A novel method of overvoltage suppression due to de-energization of shunt reactor in high voltage system - Al-Tak, Mazyed A.; Ain, Mohd Fadzil Bin; Al-Yozbaky, Omar Sh.; Jamil, Mohamad Kamarol Mohd (Institute of Advanced Engineering and Science, 2023)
Substations usually employ shunt reactors to reduce the reactive power of systems. Due to current chopping when the shunt reactor is shut off, a high frequency and amplitude overvoltage is generated. This study was aimed at eliminating switching-related overvoltages in shunt reactors so as to maintain the equipment, prevent insulation failure, and avoid reignition. Therefore, the circuit was modified according to the suggested mitigation strategy to verify that transient overvoltages are suppressed by the circuit breaker and shunt reactor. With a view to evaluate the existing chopping caused by the switching of reactor bank, the alternative transients program (ATP-Draw) model was used to simulate the transients resulting from switching a shunt reactor. This work has been put into practice for various current chopping values. The collected results of the simulation showed that the proposed model was significantly highlighted for the suppression of overvoltages, with the voltage across the circuit breaker being reduced from 679 KV to 478 KV at a current chopping value of 5 A and from 351 KV to 152 KV across the shunt reactor.